2005
DOI: 10.1016/j.str.2004.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Vertebrate Filamin Dimerization

Abstract: Filamins are essential in cell motility and many developmental processes. They are large actin cross linking proteins that contain actin binding domains in their N termini and a long rod region constructed from 24 tandem Ig domains. Dimerization is crucial for the actin crosslinking function of filamins and requires the most C-terminal Ig domain. We describe here the crystal structure of this 24th Ig domain (Ig24) of human filamin C and show how it mediates dimerization. The dimer interface is novel and quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
124
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 44 publications
10
124
0
Order By: Relevance
“…Filamin interacts with F-actin and functions to aid in the stabilization of the muscle cytoskeleton and helps with transmitting chemical signals at the Z-line (Wang and Singer, 1977;Clark et al, 2002). The dimerization of filamin is essential for the interaction of filamin with F-actin (Pudas et al, 2005). Extreme proteolytic differences in the degradation of filamin were observed between classification groups where low star probe samples had significantly less intact filamin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filamin interacts with F-actin and functions to aid in the stabilization of the muscle cytoskeleton and helps with transmitting chemical signals at the Z-line (Wang and Singer, 1977;Clark et al, 2002). The dimerization of filamin is essential for the interaction of filamin with F-actin (Pudas et al, 2005). Extreme proteolytic differences in the degradation of filamin were observed between classification groups where low star probe samples had significantly less intact filamin.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that the removal of the 109 AA from the carboxy-terminal end in degraded filamin could be the first cleavage of intact filamin observed in postmortem muscle. The carboxy-terminal end of filamin is responsible for dimerization and interaction with other cellular components such as β integrins, androgen receptors, and portions of potassium channels (Stossel et al, 2001;Feng and Walsh, 2004;Pudas et al, 2005;Nakamura et al, 2011). Therefore, the loss of this carboxy-terminal end causes the loss of ability for this protein to form dimers and impairs anchoring to the Z-line and could impair the structural integrity of the internal architecture of the muscle cell.…”
Section: Discussionmentioning
confidence: 99%
“…FLNA and FLNB are built up of an N-terminal actin-binding domain which is followed by 24 immunoglobulin (Ig)-like repeats, interrupted by two hinge regions. Homo- and heterodimerization of FLNA and FLNB occur via their carboxyl-terminal Ig-like repeat [14]. A recent study showed that FLNA and FLNB expression is reciprocally regulated with opposing effects on actin dynamics and cell spreading [15].…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant isoform of the family, FlnA, is encoded by the X chromosome in humans and mice (Feng and Walsh, 2004;Robertson, 2005). FlnA is composed of an N-terminal actin-binding domain followed by 24 Ig repeats, the C-terminal of which mediates their dimerization (Pudas et al, 2005). Human melanoma cells that lack FlnA have poor motility and continuous membrane blebbing (Cunningham et al, 1992;Flanagan et al, 2001).…”
mentioning
confidence: 99%